Mechanical performance of pe reinforced with graphene nanoplatelets (GNPs): Effect of composition and processing parameters - Zainab Al-Maqdasi; Guan Gong; Nazanin Emami; Roberts Joffe (Nanocomposites)
Processing parameters of melt mixing (one of the most conventional techniques in polymer processing) play a significant role in the quality and properties of the resulting material, especially when nanoreinforcements are involved. The current study investigates varying processing temperature, rotation speed and elements of the screw extruder, aiming to enhance mechanical properties of polyethylene (PE) nanocomposites by improving dispersion of nanoparticles from a commercial masterbatch in two grades of PE. The study investigates the effect of a common compatibilizer (MAPE) and shearing forces at varying amounts of graphene nanoplatelets (GNPs) in polyethylene. A comparison is made on mechanical properties, morphology, and changes in the microstructure. Results show that increasing amounts of GNPs lead to expected continuous increase of mechanical properties with reference to the base polymer. Addition of MAPE did not result in significant improvement in the performance of the studied systems. Use of stronger shear forces resulted in mostly negative impact on the properties.